Serum neopterin levels in patients with brucellosis - Akbulut, HH; Celik, I; Akbulut, A; Yuce, P; Kiliç, SS (W B Saunders Co Ltd, 2005)
Objectives. The aim of this study was to evaluate the importance of neopterin levels in brucellosis and its alterations with treatment. Methods. Thirty patients who had positive clinical findings, Brucella standard tube agglutination tests and/or positive blood culture were included in the study. The control group was composed of 30 healthy subjects. Neopterin (NPT) levels were measured by ELISA according to the protocol of manufacturer. Results. Mean NPT levels were 54.15 +/- 33.7 nmol/l in study groups and 8.75 +/- 2.48 nmol/l in controls (P<0.001). It was determined that NPT levels measured at the time of admission of the patients had a linear correlation between the duration of complaint (r=0.560, P=0.001). White the mean NPT levels in patients with complaints of over 30 days were 79.07 +/- 34.9 nmol/l and it was 39.71 +/- 23.4 nmol/l in the patients with complaints of less than or equal to 30 days (P=0.002). NPT values measured after treatment (20.48 +/- 25.6) was determined tower by statistical means than the values measured before treatment (54.15 +/- 33.7, P=0.0001). The NPT levels of patients with positive blood culture (75.56 +/- 33.6) were higher than those of with negative blood cultures (32.72 +/- 15.2, P=0.001). Conclusion. It was concluded that the NPT levels were higher in patients with brucellosis. In addition, it was found that the levels of NPT were higher in nonresponding patients than responded to the brucellosis treatment. It was thought that monitoring NPT levels could be useful for the extent and activity of the disease. (C) 2004 The British Infection Society. Published by Elsevier Ltd. All rights reserved.
13th European Congress of Clinical Microbiology and Infectious Diseases -- MAY 10-13, 2003 -- GLASGOW, SCOTLAND
Keywords: brucellosis; neopterin levels; monitoring therapy